“Comment” As A Development Of Marine Tourism And Flood Disaster Management Based On Go Green At Blendung Beach - Mohammad Nur Khaqiqi; Luqman Haqiqi Amirulloh (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The phenomenon of tidal waves in coastal areas is a common thing. The Keramat Sari beach is no exception(people are familiar with Blendung beach) which is located in Blendung Village, Ulujami District, PemalangRegency. Around the Pantura, almost every year there are high and low tidal floods. This tidal flood even enteredthe houses of the residents. Rob at Blendung Beach has occurred since April until now (November), and reachedthe highest rob reaching an adult's foot on June 3, 2020. This tidal flood has greatly impacted the sustainabilityof Blendung Beach tourism in terms of the economy of the residents who manage and sell on Blendung Beach.Moreover, with the Covid-19 pandemic, which has made the economy decline so that the problem is even morecomplicated. Therefore, the author offers an idea in the form of